1444 Is FBC Being Investigated Within 32 Hours of Surgery in Neck of Femur Fractures?. (12th October 2021) - Lammin, K; Dhingra, M; Mishra, P; Narayan, P; Tenang, L A H
Abstract: Introduction: The UK treats approximately 76, 000 neck of femur (NOF) fractures annually (NHFD 2018). These patients are known to be frail and dehydrated upon arrival to the emergency department. Surgery can expose patients to substantial blood loss both preoperatively and postoperatively (Foss et al). Furthermore, studies have shown that postoperative anaemia is detrimental in patients who have had hip surgery (Marval et al 2014). Thus, it is imperative to monitor patients' haemoglobin (Hb) levels immediately after the operation so that optimum treatment can be assured. The current audit standard in our local trust states that all patients must have their full blood count (FBC) within 32 hours post-surgery. As Covid-19 has brought disruption to the NHS, It is important for us to highlight any issues that arise in the monitoring of Hb in the post-operative phase of these NOF patients. Method: Using retrospective analysis, this study analysed the number of patients having the FBC within 32 hours post-surgery during the pandemic (n = 60) and was compared to a similar cohort pre-pandemic (n = 139). Results: 91% of patients overall had their Hb checked within 32 hours. 92% in the pre-covid group had a Hb check within time compared to 81% in the covid group. The risk ratio calculated was 1.5. Conclusions: Conclusively, patients in the covid group were 1.5 times more likely to have their FBC checked past 32 hours post-surgery. However, this finding was not significant. Overall, the audit standard was not met.